2014
DOI: 10.5194/asr-11-41-2014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical models sea surface wind compared to scatterometer observations for a single Bora event in the Adriatic Sea

Abstract: Abstract.We compare the sea surface wind fields forecasted by a Global Circulation Model (GCM) and three Limited Area Models (LAMs) in an operational-like set-up, with the wind remotely sensed by the NASA QuikSCAT scatterometer. The comparison is performed for a single case of Bora wind in the Adriatic Sea, with the purpose to understand the ability of the model forecasts in reproducing the mesoscale features captured by the scatterometer, and to investigate on the suitability of LAM and GCM forecasts as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This is a requirement given by the general underestimation of ECMWF winds in the Mediterranean Sea (Zecchetto & De Biasio, 2007). The characteristics of these biases do not seem to be peculiar to the ECMWF global model, but are exhibited also by other atmospheric models (De Biasio, Miglietta, & Zecchetto, 2014). A relatively small part of the bias is possibly ascribed to the scatterometers themselves: in the present work we have used QuikSCAT, Oceansat-2, ASCAT-A and ASCAT-B data, and small biases are normal between different datasets.…”
Section: Discussionmentioning
confidence: 98%
“…This is a requirement given by the general underestimation of ECMWF winds in the Mediterranean Sea (Zecchetto & De Biasio, 2007). The characteristics of these biases do not seem to be peculiar to the ECMWF global model, but are exhibited also by other atmospheric models (De Biasio, Miglietta, & Zecchetto, 2014). A relatively small part of the bias is possibly ascribed to the scatterometers themselves: in the present work we have used QuikSCAT, Oceansat-2, ASCAT-A and ASCAT-B data, and small biases are normal between different datasets.…”
Section: Discussionmentioning
confidence: 98%
“…The experience gained in the Adriatic Sea by using the data of some of the available LAM demonstrated that they do not provide performances better then those of ECMWF (De Biasio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors (e.g. Miglietta et al, 2012;De Biasio et al, 2014) also argue that local models could show more details (more detailed flow patterns) although worse statistics due to errors in timing and location, whilst global models would produce smoother results and probably much skillful forecasts. At this point, the computational cost would indicate which should be the atmospheric model to be considered depending on the skill assessment requirements.…”
Section: Final Remarksmentioning
confidence: 99%